1965
DOI: 10.1021/bi00879a034
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Fluoropyruvate as a Substrate of Lactate Dehydrogenase*

Abstract: There are conflicting reports in the litera-Purified fluoropyruvate has been shown to be a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1965
1965
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In addition, the isolation of lid mutants of B. stearothermophilus amongst fluoropyruvate-resistant strains suggests that in this organism one mode of fluoropyruvate toxicity is dependent on its initial conversion to fluorolactate, in contrast to previous reports of the effect of this and similar fluoroanalogues on E. coli [10]. We have, in fact, shown (Payton, M.A., unpublished) that fluoropyruvate is a substrate, albeit a poor one, for semipurified LDH from B. stearothermophilus, as has been reported for LDHs from other sources [11].…”
Section: Resultssupporting
confidence: 61%
“…In addition, the isolation of lid mutants of B. stearothermophilus amongst fluoropyruvate-resistant strains suggests that in this organism one mode of fluoropyruvate toxicity is dependent on its initial conversion to fluorolactate, in contrast to previous reports of the effect of this and similar fluoroanalogues on E. coli [10]. We have, in fact, shown (Payton, M.A., unpublished) that fluoropyruvate is a substrate, albeit a poor one, for semipurified LDH from B. stearothermophilus, as has been reported for LDHs from other sources [11].…”
Section: Resultssupporting
confidence: 61%
“…The two 0.5 cm reaction cells contained identical solutions with the blank and were mixed with a syringe to start the reaction. A value of 6000M-'cm-' was used for the molar absorption coefficient of the adduct with pyruvate (Gutfreund et al, 1968) and 6250M-1 *cm-' for the adduct with fluoropyruvate (Eismann et al, 1965). There was no detectable formation of adduct in the absence of lactate dehydrogenase at the pH used for these assays.…”
Section: Methodsmentioning
confidence: 99%
“…However, it was important to establish that the modified lactate dehydrogenase was still able to catalyse adduct formation under suitable conditions. Table 3 shows the results of experiments carried out in an attempt to demonstrate adduct formation with both pyruvate and the substrate analogue fluoropyruvate (Eisman et al, 1965). It was not possible to detect the formation of any 325 nm-absorbing adduct by the modified lactate dehydrogenase and pyruvate as the substrate, whereas fluoropyruvate was able to form stoicheiometric amounts of adduct with both the native enzyme and the thiomethylated enzyme.…”
Section: Adduct Formation Between Nad+ and Pyruvatementioning
confidence: 99%
“…Adduct formation between pyruvate or fluoropyruvate and NAD+ catalysed by native and thiomethylated lactate dehydrogenase Using the split-cell technique in a Cary 118 spectrometer the increase in A325 was measured in the reaction cells containing lactate dehydrogenase (313 ug/ml), NAD+ (0.25mM) and various concentrations of pyruvate or fluoropyruvate in 0.1 M-potassium phosphate buffer, pH 7.0 at 23°C. A value of 6250 litre * molP * cm-l was used as the molar absorption coefficient at 325nm for the enzyme-bound adducts (Eisman et al, 1965 Comparison of the thermal stability of native and thiomethylated lactate dehydrogenase It had previously been observed that the modified lactate dehydrogenase was inactivated by dilution (Bloxham & Wilton, 1977) and therefore it was of interest to compare also the thermal stability of the native and modified enzymes. Denaturing conditions were chosen that were identical with those reported by Kapmeyer & Pfleiderer (1977) for studying the thermal stability of pig heart lactate dehydrogenase in which surface lysine residues had been modified.…”
Section: Adduct Formation Between Nad+ and Pyruvatementioning
confidence: 99%